Percipient power and US-Chinese competition in the post-Covid 19 world - Hussein Kazem Al-Hamam, Lecturer, Dr. Ali (The college of law and political science journal, 2023)
The increase of careing in the power topic at the modern era has led it to morecomplexity. That’s make experts giving this topic more attention. Therefore theimportance of our research is to focus on how to measure power and its impactRQWKHIXWXUHRIFRPSHWLWLRQ6RDVERWKRI&KLQDDQGWKH8QLWHG6WDWHVKDYHPDQ\HOHPHQWVRISRZHUZKLFKLWPDNHWKHPÀUVW7KHUHIRUHWKURXJKWKLVSDSHUZHZLOOinitially raise a number of questions that may lead us through the research pagesto some logical results, like:How did the different experts interpret their visions of the concept of power?And what is the main elements that effected on it?How the power measure? And what is the Percipient power?+RZZHFDQDQDO\]HWKHFRPSHWLWLRQEHWZHHQ86DQG&KLQDDQGZKDWLVWKHpower elements of each of them?